1966
DOI: 10.2105/ajph.56.12.2033
|View full text |Cite
|
Sign up to set email alerts
|

Admission and prevalence rates for psychiatric facilites in four register areas.

Abstract: The use of a psychiatric case register for research is reported, with specific attention to the use of psychiatric services in four areas. Rates were obtained by demographic variables and by diagnostic classification, as well as for one day prevalence, one year admissions, and one year prevalence. Further studies based on such registers are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1971
1971
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…Ancient literature from U.S. mentions schizophrenic reactions as the predominant admission diagnosis, alcoholic disorders the next and depressive reactions the least. 2 In one of the study from England, depression and anxiety were the most common reason for hospital admission, accounting for 29.6% of all admissions, schizophrenia and related psychoses accounted for 26.0% of admissions, substance misuse 19.1% and others 12.2%. 3 Previous epidemiological studies from India have found the most common disorders in community as affective disorders / anxiety neurosis, followed by alcohol use disorders, mental retardation, epilepsy and schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
“…Ancient literature from U.S. mentions schizophrenic reactions as the predominant admission diagnosis, alcoholic disorders the next and depressive reactions the least. 2 In one of the study from England, depression and anxiety were the most common reason for hospital admission, accounting for 29.6% of all admissions, schizophrenia and related psychoses accounted for 26.0% of admissions, substance misuse 19.1% and others 12.2%. 3 Previous epidemiological studies from India have found the most common disorders in community as affective disorders / anxiety neurosis, followed by alcohol use disorders, mental retardation, epilepsy and schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
“…A running case register may be a useful tool to produce comprehensive information about the changing picture of psychiatric care in a defined area and its effect on the utilization of services (1)(2)(3)(4)(5)(6)(7)(8).…”
mentioning
confidence: 99%
“…Desegregation did not occur in a static environment. Maryland, like most other States, has 3, 303,343 2, 740, 185 563, for some time been engaged in a program to develop and employ new treatment concepts and modalities, to improve staff-patient ratios, and to construct new facilities (6). While the net effect of these changes cannot be gauged, our observation has been that they occurred fairly uniformly in the four hospitals studied.…”
Section: Methodsmentioning
confidence: 99%